FORMATION AND DEVELOPMENT OF THE SYSTEMATIZATION OF THE MILITARY LEGISLATION OF UKRAINE - Kaliuzhniy, Rostyslav; Aliiev, Roman (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: to study the origins of the formation and development of systematization of military legislation of Ukraine, to analyze the process of military lawmaking as an important element of the national legal heritage, which is based on the military-legal consciousness of the Ukrainian people. Research methods: documentary analysis and synthesis, comparative analysis, objective truth, cognitive-analytical, intersectoral method of legal research, logical methods that have been used as tools to achieve this goal. Results: addressing the historical and legal stages of the formation of military lawmaking will provide an opportunity to gain knowledge on improving the mechanism of systematization of military legislation of Ukraine. Discussion: on the basis of the received data the historical-legal and normative aspects of development of systematization of the military legislation in Ukraine are analyzed, the stages of systematization of norms of the military law are investigated. We believe that the study of the origins and stages of formation and development of systematization of military legislation of Ukraine will provide an opportunity to identify further ways to solve the problem of codification of legislation in the field of defense of Ukraine, as military law together form a significant part of current national legislation. Examining the current legal norms, we can note that they are established by different public authorities, at different times on any issue and included in the normative sources of different legal force. As a result, on the one hand there is a need to ensure their unity and interaction, and on the other hand - the interests of practical legal activities (labor relations, civil or military service) require their systematization in certain groups of social relations. The process of systematization of the norms of the current legislation of Ukraine does not bypass the military sphere as a significant group of military-public relations. Defining the role and place of systematization in the Ukrainian military law-making, we can note that the systematization of military legislation is an organic unity of various historical stages, which as an objective expression of the processes of change and development of socio-economic and military-political relations in Ukraine and the development of military law in Ukraine. Thus, the analysis of the origins of the formation and development of systematization of military legislation of Ukraine made it possible to conditionally determine four stages of systematization of military legislation: the first stage (XIV-XVIII centuries), the second stage (XIX – early XX centuries), the third stage years of the XX century to July 16, 1990), the fourth stage (the period from August 24, 1991 to the present day).